FARMER SATISFACTION ANALYSIS ON RICE FARMING INSURANCE PROGRAM IN TEGAL REGENCY - Mirza Andrian Syah; Mukson Mukson; Wiludjeng Roessali (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
Farmers satisfaction in joining Rice Farming Insurance illustrates the program performance. The satisfaction of Rice Farming Insurance program can be measured through some attributes of satisfaction. Satisfaction attributes are assessed ranging from dissatisfied to very satisfied. This research aimed to determine the level of farmer satisfaction on Rice Farming Insurance program. This research was conducted in January – February 2020. Slovin method used for sampling method with total sample of 100 respondent, consist of 53 respondents were taken in Dukuhwaru District and 47 respondents were taken in Warureja District using proportional allocation. Locations in this research was choose with purposive method. Importance Performance Analysis and Customer Satisfaction Index were used to analyze. The result showed that Farmers were satisfied with the implementation of the Rice Farming Insurance program with CSI score of 79%. The attributes that need to be improved are the compensation requirements, the amount of coverage, the submission procedure, reviewing, and payment procedure of claims, and the time of approval and payment of claims. Those attributes were considered important by farmers yet still have low performance.